1977
DOI: 10.1111/j.1469-8137.1977.tb04848.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Light Intensity on Acetylene Reduction by Blue‐green Algal Mats in Sub‐tropical Grassland

Abstract: SUMMARYHigh light intensities such as those found during the middle of the day in southern Africa are not responsible for inhibition of acetylene reduction by mats of blue-green algae in kikuyu lawns. Similar results were obtained with uni-algal cultures of Nostoc isolated from the algal mats. Short term experiments (3 h) with both cultures and algal mats showed a direct relationship between acetylene reduction and light intensities of up to 323 lux but no significant increase in acetylene reduction for light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that potential nitrogen fixation in biocrusts is highly dependent on past and present water and light regimes, ambient temperature, water content and light intensity (Belnap, 2003;Jones, 1977bJones, , 1977cJones, , 1977dKallio and Kallio, 1978;Rychert et al, 1978). In addition, some studies have also demonstrated that potential fixation rates vary with the successional stage of biocrusts (Belnap, 1996(Belnap, , 2002Housman et al, 2006;Marsh et al, 2006), as both species and biomass of N-fixing organisms change during the successional process (Belnap, 2003;Kallio and Kallio, 1978;Marsh et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have shown that potential nitrogen fixation in biocrusts is highly dependent on past and present water and light regimes, ambient temperature, water content and light intensity (Belnap, 2003;Jones, 1977bJones, , 1977cJones, , 1977dKallio and Kallio, 1978;Rychert et al, 1978). In addition, some studies have also demonstrated that potential fixation rates vary with the successional stage of biocrusts (Belnap, 1996(Belnap, , 2002Housman et al, 2006;Marsh et al, 2006), as both species and biomass of N-fixing organisms change during the successional process (Belnap, 2003;Kallio and Kallio, 1978;Marsh et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…A species of Nostoc isolated from the algal mats was also used (Jones, 1977c). Acetylene reduction was measured as described previously (Jones, 1977c).…”
Section: ?^ Algae and Measurement Of Acetylene Reductionmentioning
confidence: 99%
“…The highest rates of diurnal acetylene reduction are found in the afternoon when both soil temperature and light intensity are below the levels at midday when acetylene reduction is low. Light intensity does not appear to contribute to this midday drop in acetylene reduction (Jones, 1977c) hence there is the need for an investigation into the effects of temperature on acetylene reduction by the algal mats.…”
Section: Introductionmentioning
confidence: 99%